2021
DOI: 10.1038/s41598-021-84918-y
|View full text |Cite
|
Sign up to set email alerts
|

Screening pregnant women in a high-risk population with WHO-2013 or NICE diagnostic criteria does not affect the prevalence of gestational diabetes

Abstract: There are currently several diagnostic criteria for gestational diabetes (GDM). Both the WHO -2013 and NICE diagnose GDM based on a single step 75 g OGT; however; each uses different glucose thresholds. Previous studies have shown that the prevalence of GDM using the NICE criteria (GDM-N) is lower than that using the WHO-2013 criteria (GDM-W). Qatar has national diabetes in pregnancy program in which all pregnant women undergo OGTT screening using the WHO-2013 criteria. This study aims to define the prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
3
9
0
2
Order By: Relevance
“…Of the 44 993 studies identified, 156 studies,2324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115116117118119…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Of the 44 993 studies identified, 156 studies,2324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115116117118119…”
Section: Resultsunclassified
“…Of the 44 993 studies identified, 156 studies, 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 …”
Section: Resultsunclassified
“…also reported an increased risk of adverse perinatal outcomes in women with elevated fasting plasma glucose (5.1–5.5 mmol/L), who were identified as normoglycemic by the UK NICE criteria. Similarly, Bashir et al 24 . and Todi et al 25 .…”
Section: Discussionmentioning
confidence: 81%
“…This data-set has previously been reported (7) and was a convenience sample that included all women who underwent a 75 g OGTT between January 2016 and April 2016 with and without GDM at a tertiary hospital of the Hamad Medical Corporation (Women's Wellness and Research Center) in Qatar (Supplementary Table S2). This is the main maternity hospital in Qatar with 16,000-18,000 births annually.…”
Section: Doha Qatarmentioning
confidence: 99%
“…The two widely used criteria for the diagnosis of GDM rely on individual time-point thresholds on a 2-hour (5) or a 3-hour (6) glucose tolerance test (GTT), and requires elevated values at one or two time points respectively for the diagnosis. As such, the number of elevated time-point values required and different glycaemic thresholds will alter the selection of women and prevalence of GDM (7) but such changes in selection and prevalence have not, thus far, been associated with maternal or perinatal benefit overall (8;9). For a country like Denmark, changing to criteria that define GDM based on application of the International Association for the Diabetes in Pregnancy Study Group (IADPSG) 2010 (5) definition of GDM would result in a marked increase in GDM prevalence to 40% based on the fasting criterion alone, without convincing evidence of adverse pregnancy outcomes (10).…”
Section: Introductionmentioning
confidence: 99%